Finite element analysis of the effect of weld geometry and load condition on fatigue strength of lap joint - Li, X.Y.; Partanen, T.; Nykänen, T.; Björk, T. (The International journal of pressure vessels and piping, 2001)
Many welded lap joints are subject to fluctuating loads, and fatigue failure plays a dominant role in the failure of such structures. Based on the concepts of linear elastic fracture mechanics, the effects of weld geometry, load conditions and the boundary constraints on fatigue strength of a ferrite–pearlite steel lap joint were investigated in this paper using the finite element method. Paris's power law was used to predict the fatigue life of the joints. Various weld geometry including the leg length, flank angle and the size of lack-of-penetration were considered during the calculation of fatigue strengths. The loads include tension, bending and their combinations. It was found that the existence of a root crack has no influence on the fatigue strength of the joint, under the relevant load conditions. The existence of a toe crack is also of no influence on the fatigue strength of the joint if the applied loads, e.g. DOB>0 in this paper, produce a compressive stress field at the top region of the main plate. For a lap joint with a free transverse ( Y direction in this paper) boundary constraint at the main plate, a joint with a smaller size of lack-of-penetration, a reasonably large weld leg and smaller flank angle is recommended to be used in engineering practice, in order to obtain a higher fatigue strength. For a lap joint, with transverse fixed boundary constraint at the main plate, the fatigue strength increases with a decrease of weld size but the influence of flank angle depends on the type of load carried. It was also found that the size reduction in FE model is a significant influence on the calculated fatigue strength; the use of reduced size FE model gives a much higher overestimate of fatigue strength of the joint.